Corporate governance and public reprimand - Zaini Embong,; Ruhaznawati Md Rudzi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Public reprimand is a form of enforcement actions taken by Bursa Malaysia against companies that violate listing requirements, with intention to deter future breach and to cultivate good standards of corporate governance and businessconduct in the market. Corporate governance is put in place to ensure that companies are managed to the best interest of shareholders. Empirical evidences show that corporate governance and enforcement actions are significantly related. However, none of the studies are done in Malaysian setting. The nature of capital market and the rules and regulations of relevant authority are different from country to country. Hence, it is important to investigate whether enforcement actionsis also related to corporate governance in Malaysia. When companies were reprimanded, their reputations and most often share prices will be affected, compromising the wealth of shareholders. If actions were not taken by the relevant authority, confidence in the market may subside and this will affect the development of capital market. The reprimand should also serves as educating mechanism in which the affected companies are expected not to repeat the same offence. This has yet to be investigated. This study therefore extends existing knowledge on public reprimand by providing empiricalevidence on Malaysia setting and more importantly whether or not public reprimand serves as educating mechanism. This study employs a cross-section, match-pair design with a sample of 110 companies. Results from logistic regression indicate that there are significant differences in board characteristics between companies that have been reprimanded and those which are not. The test on board characteristics two years after public reprimand however shows that there is no significant changes in board characteristics. Small sample size is among limitations of this study. The findings give insight on the role of enforcement actions in regulating companies and what need to be done by authority.